Perhitungan Premi Asuransi Pertanian Padi Terhadap Indeks Curah Hujan di Kabupaten Aceh Utara - Dara Irsalina; Ahmad Hadra Zuhri; Rini Oktavia; Komang Nonik Afsari Dewi; Farhani (Mathematics Study Program, Faculty of Mathematics and Natural Science, Udayana University Gedung UKM, Ruang UKM 8 Lt 1, Kampus Bukit Jimbaran, Badung-Bali., 2025)
Northern Aceh stands as a crucial pillar of Aceh's economy, particularly in the agricultural sector. However, since 2019, agricultural production in Northern Aceh has been declining due to climate change, resulting in significant losses for many farmers in the region. This study aims to calculate the rice crop insurance premium against the rainfall index in Northern Aceh using the Black-Scholes model, assuming no transaction costs and a constant interest rate. By using rainfall and rice productivity data from 2020 to 2023, the results show that the premium to be paid by farmers is IDR 3,615,559 when the rainfall trigger value is 42.01mm. Conversely, when the trigger value is 44.40mm, the premium increases to IDR 3,710,713. This indicates that as the rainfall value increases, the premium that must be paid also rises.